2017
DOI: 10.3390/ijerph14101123
|View full text |Cite
|
Sign up to set email alerts
|

How Does Patient Safety Culture in the Surgical Departments Compare to the Rest of the County Hospitals in Xiaogan City of China?

Abstract: Objectives: Patient safety culture affects patient safety and the performance of hospitals. The Hospital Survey on Patient Safety Culture (HSOPSC) is generally used to assess the safety culture in hospitals and unit levels. However, only a few studies in China have measured surgical settings compared with other units in county hospitals using the HSOPSC. This study aims to assess the strengths and weaknesses of surgical departments compared with all other departments in county hospitals in China with HSOPSC. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
2
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
1
16
2
16
Order By: Relevance
“…Estas áreas estão relacionadas com os supervisores, que desempenham papel importante no auxílio das equipes quanto ao estabelecimento de uma cultura com qualidade e ambiente seguro. A boa liderança é um dos maiores incentivos para melhorar a comunicação e fortalecer a CS (Wang & Tao, 2017).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Estas áreas estão relacionadas com os supervisores, que desempenham papel importante no auxílio das equipes quanto ao estabelecimento de uma cultura com qualidade e ambiente seguro. A boa liderança é um dos maiores incentivos para melhorar a comunicação e fortalecer a CS (Wang & Tao, 2017).…”
Section: Discussionunclassified
“…Nota-se grande preocupação dos profissionais de que os seus erros sejam registrados em seus arquivos ou que levem a algum tipo de punição, ainda que o hospital não estipule qualquer punição para os erros reportados. Há a crença de que eventos adversos relatados demonstram pouca habilidade, que leva à depreciação do cargo exercido, ferimento da honra ou diminuição na renda (Wang & Tao, 2017).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In several studies conducted in a different setting, front-line professionals were found to usually complain more about actions proposed by the directive staff [6]. Also, some studies have shown the sensibility of the safety culture measures to discriminate against the impact of positive actions to improve safety [19] In this case, we observe a similar pattern, although, curiously, there were not greater differences when comparing safety culture measures between quality coordinators and professionals working in smaller centers.…”
Section: Discussionmentioning
confidence: 99%